Exenatide improves ovarian and endometrial injury and preserves ovarian reserve in streptozocin induced diabetic rats. (March 2015) - Artunc-Ulkumen, Burcu; Pala, Halil Gursoy; Pala, Emel Ebru; Yavasoglu, Altug; Yigitturk, Gurkan; Erbas, Oytun
Abstract We aimed to evaluate: (1) endometrial and ovarian tissue injury caused by the glucose toxicity in diabetic rat model and (2) the effect of GLP-1 analog (exenatide) on endometrial and ovarian diabetes induced injury with emphasizing the underlying mechanism. The study group composed of 24 female rats assigned randomly into 3 groups. Group 1 was the control group (n = 8) and received no treatment. Diabetes was induced by intraperitoneal injection of streptozocin for 16 rats which are further assigned randomly into 2 groups: 1 ml/kg intraperitoneal saline was given to Group-2 (diabetic non-treated control group, 8 rats) and 10 µg/kg/day of intraperitoneal exenatide was given to Group 3 (exenatide treated group, 8 rats) for four weeks. After four weeks, blood samples were collected and hysterectomy with bilateral oophorectomy was performed for histopathological examination. Diabetes caused endometrial and ovarian tissue injury in rats (p < 0.0001). Serum transforming growth factor beta (TGF-ß), malonylaldehyde (MDA), pentraxin-3 (PTX-3) levels were higher in diabetic rats (p < 0.0001), whereas antimullerian hormone (AMH) was lower (p < 0.001). Serum levels of these markers reflected that Diabetes induced injury in the reproductive tract occured via oxidative stress, fibrosis and severe inflammation. Diabetes diminished ovarian reserve. Exenatide treatment improved the histological degeneration and fibrosis in the endometrium and ovary with concomitant decrease in inflammatory and oxidative stress markers (p < 0.05). Exenatide also improved ovarian reserve (p < 0.05). Glucose toxicity occured severely in ovary and endometrium in DM. After exenatide treatment; ovarian and endometrial injury and fibrosis seems to decrease significantly. The effects of exenatide in rat models give hope to prevent the women with DM from premature ovarian failure and endometrial dysfunction.